925 Antibiotic Resistance and Pneumococcal Conjugated Vaccines Coverage of Streptococcus Pneumonia from Middle Ear Fluid of Children < 5 Years. (October 2012) - Falup-Pecurariu, O; Leibovitz, E; Mercas, A; Lixandru, R; Bleotu, L; Zavarache, C; Falup-Pecurariu, C; Porat, N; Dagan, R; Greenberg, D
Abstract : Aims: A prospective study was initiated in Brasov, Romania in 2009 to assess the antibiotic resistance pattern of Streptococcus pneumoniae (Pnc) isolated from middle ear fluid in children with acute otitis media (AOM) < 5years old. Methods: Patients diagnosed with AOM who underwent tympanocentesis or presented with purulent otorrhea of < 24 hours duration were enrolled. Results: 206 patients were enrolled, 132 (64%) episodes occurred in children < 2years old; 105 (51%) were culture-positive. 108 isolates were recovered: Pnc - 75 (67%), H. influenzae - 26 (24%) and others - 7 (9%). Nonsusceptibility to penicillin was found in 25/27 (93%) [MIC >1.5µg/mL]). Pnc resistance to TMP/SMX, erythromycin and clindamycin and MDR (multidrug resistance) were 22/27 (82%), 16/27 (59%), 13/27 (48%) and 15/27 (56%), respectively. Of the 39 (54%) Pnc serotyped the most common were: 19F (26%), 6B (18%), 14 (15%), 23F (15%) and 19A (8%). Penicillin highly resistant was found in 84.6% (11/13): 2–6B, 6–19F, 2–14 all included in the PCV 7-valent (PCV7), except for 2 isolates: 9A, 22F. Out of the 13 highly resistant serotypes 7 (53.84%) were multi drug resistant and all of them were 6B or 19F. 35/39 (90%) of all SP isolates are included in PCV-13. Conclusions: The proportion of penicillin resistance Pnc isolated from MEF was extremely high as well as resistance to other common antibiotics. Coverage of PCV7 and PCV10 vaccines was equal. The PCV13 coverage was 90%. Most antibiotic resistant serotypes were included in the PCV13.